Implementation of the Philippine local government code by the Barangays. - Palmares, Maria Nelva F (1997.)
The Barangay Officials attended their regular monthly meetings. They produced only one ordinance and 92 resolutions. They prepared 16 projects in their Barangay Development Plan with the help of the representatives of the PO and NGO operating in their barangay but without consultation with the constituents of their barangay. POs and NGOs were not active in the planning and development of the barangay, having only one disco as their common project in the barangay. Sources of the revenue of the barangay come from real property tax, internal revenue allotment, business tax, community tax, barangay clearance, and outside aid which are from the municipal and provincial government, national agencies, the congressman, and popular senators of our country. Donations from prominent personalities also add to the sources of revenue of the barangay. The Barangay Council were very much in favor of the Local Government Code, regarding it as a guide to them in governing their barangay, thus, upon implementing it, they attained self- relianc. The problems encountered by the barangay officials in implementing the Local Government Codee are: existing reliance on higher government units when it comes to final decision, more financial aid, incapability of local peace and order officials to handle the barangay, not complete implementation of the Code, constituents lack of orientation about the Code, difficulty and long process caused by a fuller implementation of the Code, and decreased aid from higher government officials.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Local Government Code -- Philippines